Hyperferritinemia and markers of inflammation and oxidative stress in the cord blood of HIV‐exposed, uninfected (HEU) infants. Issue 6 (27th February 2015) - Selvam, A; Buhimschi, IA; Makin, JD; Pattinson, RC; Anderson, R; Forsyth, BW
<x xml:space="preserve">Abstract</x> Objectives The purpose of this study was to evaluate markers of iron status and inflammation/oxidative stress in maternal and cord blood (CB) of HIV‐infected and HIV‐uninfected women as potential mechanisms for poor outcomes among HIV‐exposed, uninfected (HEU) infants. Methods Maternal venous blood and CB specimens were obtained from 87 pregnant women (45 HIV‐infected and 42 HIV‐uninfected) enrolled at Kalafong Hospital, Pretoria, South Africa. Iron status [serum iron, ferritin and transferrin concentrations, transferrin saturation, soluble transferrin receptor (sTfR) concentration and the sTfR/log ferritin (sTfR/F) index], antenatal exposure to inflammation (CB C‐reactive protein and interleukin‐6 concentrations and haptoglobin switch‐on status) and oxidative stress [total radical trapping ability of CB plasma (TRAP) and chronic oxidative stress (soluble receptor of advanced glycation end‐products (sRAGE) concentration] were assessed in laboratory studies. Results There were no differences between the HIV‐infected and HIV‐uninfected groups in maternal haematological and iron indices, except that HIV‐infected mothers had decreased white blood cell counts (P = 0.048) and increased serum ferritin concentrations (P = 0.032). Ferritin levels were significantly higher in CB than in maternal blood (P < 0.001) in both groups and further elevated in the CB of HEU infants (P = 0.044). There was also an inverse relationship between CB sTfR/F index and sRAGE (r = −0.43; P = 0.003) in the HIV‐infected but not in the HIV‐uninfected group. Conclusions Our study showed for the first time that ferritin was significantly elevated in CB of HEU infants. The inverse relationship between sTfR/F index and sRAGE in CB suggests that chronic oxidative stress or RAGE axis activation in HIV‐infected mothers may play a role in modulating ferritin levels.